Pipunculidae (Diptera) from southern Iran, including two new species of the genus Tomosvaryella Aczél - Majnon-Jahromi, Bahareh; Gheibi, Mehdi; Fallahzadeh, Majid; Kehlmaier, Christian; Hesami, Shahram (Zootaxa, 2017)
We provide data on the distribution of 23 big-headed fly species (Diptera: Brachycera: Pipunculidae) from Fars province, southern Iran. Two new species of the genus Tomosvaryella Aczél, T. angulata sp. nov. and T. pistacia sp. nov., are described and illustrated. The new species show a clear morphological affiliation to the T. congoana species-group that was hitherto only known from the Afrotropical region. Nine species recorded herein represent first records for Iran. The number of pipunculid species recorded from Iran is now raised to 30. By DNA barcoding of the mitochondrial COI gene, males and females could be unequivocally associated with each other for most species.